Effect of Cellulose Acetate Phthalate (CAP) on Characteristics and Morphology of Polysulfone/Cellulose Acetate Phthalate (PSf/CAP) Blend Membranes - Asmadi, Ali; R. M., Yunus; Mohamad, Awang; Anwar, Johari; Ramli, Mat (Trans Tech Publications Inc., 2014)
Polysulfone (PSf) membrane is catogorized as hydrophobic membrane that easily fouled during membrane operation process. The presence of second hydrophilic polymer which added into membrane casting solutions plays a crucial role in adjusting the membrane properties. This hydrophilic polymer was employed in hydrophobic polymer membranes in order to improve hydrophilicity and performance as well as formed antifouling ultrafiltration (UF) membranes. In this study, a hydrophilic polymer, cellulose acetate phthalate (CAP) was added into polysulfone (PSf) membrane casting solutions by blending technique to produce PSf/CAP blend membranes. Flat sheet asymmetric PSf/CAP blend membranes were prepared by wet phase inversion method. The results revealed that an increase in CAP increased the hydrophilicity properties of PSf/CAP blend membranes compared to pure PSf membrane. The significant changes in size and numbers of microvoids and macrovoids in the morphological structures of PSf/CAP blend membranes were due to CAP promote the instantaneous liquid-liquid demixing during phase inversion process.